Expected Transport Accessibility Improvement and House Prices: Evidence from the Construction of the World's Longest Undersea Road Tunnel - Štěpán Mikula; Peter Molnár (Masaryk University, Faculty of Economics and Administration, 2022)
This paper studies the impact of expected transport accessibility improvement on house prices. We identify the effect exploiting a quasi-natural experiment created by the approval and construction of the Ryfast tunnel system in Rogaland, Norway, which shortened the travelling time to the affected municipality from 62 to 24 minutes. Estimates of a repeated sales model in a difference-in-differences framework show that the expectation of improvement in transport accessibility connected with the construction of the tunnel system led to an increase in house prices by 10.1–12.8% on average. That effect grew as the opening of the tunnel drew closer and was driven by less valuable houses.
Keywords: R3; R4; 330; transport accessibility; expectations; house prices; Ryfast tunnel system; construction; Norway